General aspects of providing raw or cooked alternative food for dogs (Research, Society and Development, 2022)
Currently, there is an increasingly humanized connection between companion animals, and this is reflected in the food provided to the animals. There is a tendency on the part of tutors to want to offer a diet closer to their food (cooked food) or to provide a diet closer to canine ancestry (raw food). Therefore, the objective of this literature review is to present the positive and negative points of food provided raw or cooked for dogs and cats. A search of scientific publications published from 2009 to 2022 was carried out. How the following platforms were carried out: CAPES, PUBMED and ACADEMIC GOOGLE. Diet-related zoonotic articles can exist with both the animal and the tutor potential. In relation to the cooked diet, they do not identify with the presence of animals, often do not meet the nutritional requirements. Thus, to seek information from the tutor to professionals so that the diet together are not risks of animal nutrition and neither to the tutor, be it of that, as nutritional requirements.